Estimation Of Gas Exchange Parameters In Backcross Introgressed Lines Of Rice (Oryza Sativa L.) With Different Combinations Of Drought Qtls (Applied Biological Research, 2016)
The present investigation was carried out to study the gas exchange  parameters in backcross inbred lines of ‘Improved White Ponni’ (IWP)  introgressed with different drought yield QTLs and their parents raised  under control and stress conditions. Various gas exchange parameters  and single plant yield were observed using portable photosynthetic  system (infra red gas analyser - IRGA). Among the genotypes, three  combination of QTL line IWP-4-2 recorded significantly higher  photosynthetic rate (22.97 μ mol CO2 m-2 s-1), stomatal conductance  (0.36 mol H2O m-2 s-1), transpiration rate (6.25 mmol H2O m-2 s-1),  internal CO2 concentration (240.82) ratio between internal and  atmospheric CO2 concentration (0.25) and single plant yield (15.11)  which was on par with the tolerant parent Apo (an high yielding indica  cultivar moderately tolerant to drought stress) under severe moisture  stress regime. Overall study clearly revealed that, the performance of  introgressed line with three drought QTLs (IWP-4-2) was better than  two drought QTL introgressed lines of IWP-1-52 and IWP-1-57. Results  from graphical genotyping using three foreground and 36 polymorphic  background markers revealed that, the three QTL introgressed line  IWP-4-2 had 72.20% genome recovery from Improved White Ponni,  13.89% from APO and 13.89% heterozygous region.
Keywords: Drought; graphical genotypes; photosynthetic rate; rice; stomatal conductance; transpiration rate